Distal biceps tendon repair and posterior interosseous nerve injury: clinical results and a systematic review of the literature - Silvio Chiossi; Marco Spoliti; Pasquale Sessa; Valerio Arceri; Attilio Basile; Francesca Romana Rossetti; Riccardo Maria Lanzetti (Medicinski glasnik, 2020)
Aim: To report clinical, functional and radiographic results of oneincision distal biceps tendon repair with Toggle Loc (Zimmer-Biomet, Warsaw, Indiana, USA) at an average 4-year follow-up and to assess posterior interosseous nerve injury complications after reconstruction. Methods: We conducted a retrospective review of 58 consecutive distal biceps tendon repairs performed at our department between 2010 and 2018. Disabilities of Arm, Shoulder and Hand (DASH) score, Visual Analogue Scale (VAS) scale and elbow range of motion (ROM) were recorded at each follow-up and an ultrasound examination was also performed to assess the repaired biceps brachii tendon. Results: Clinical evaluation showed good and excellent results at medium- and long-term follow-up. A temporary posterior interosseous nerve (PIN) palsy developed in four (6.81%) patients and always resolved in 8 weeks. PIN palsy prevalence is in accordance with the results of the previous studies. Conclusion: Distal biceps tendon repair with Toggle Loc is an effective surgical procedure. PIN injury is a relatively rare complication after one-incision anterior repair. Our complication rate did not differ significantly from other studies that have used cortical button fixation, reported in current literature. Our results confirm that accidental injury of PIN may also happen to experienced surgeons and suggest extreme care and an appropriate surgical technique to reduce this iatrogenic risk.
Keywords: radial nerve lesion; surgical repair; sport trauma; tendon avulsion